Governmentality, Modernity and the Historical Politics of Ò ̣yọ-Hegemony in Yorùbá ́ Transnational Revivalism - Clarke, Kamari Maxine (Anthropologica, 2022)
In this essay, I argue that it was the influence of transnational forms of knowledge in Nigeria—the shift from indigenous oral forms to accessible circulating literary writings—which facilitated the generative locus of power that led to the privileging of Oyo-Yoruba ancestry as the popular literary icon of African American revivalism. With the increasing significance of late nineteenth century scientific inquiries deployed by native-born Africans, a newly developing Nigerian elite participated in the documenting of human sciences and thereby contributed to the invention of a particular type of "Yoruba history." This process, mediated by the temporalities of modern subjectivities, led to the standardization of "the Yoruba" as we know them and was allied with the development of the Nigerian nation. In examining changes in social meanings over time, I examine what changes and which canonical tenets must remain the same for new meanings to be seen as legitimate. I demonstrate that these fields are embedded in historically complex webs of power that code geographic and temporal meanings in particular ways